Les dimensions géopolitiques du processus de rénovation politique en Equateur - Alexis Sierra (EchoGéo)
After ten years of political instability, Ecuador seems to pass through a new period after the Rafeal Corea presidential election (2006). This article try to deal with the new electoral geography of this country and the different strenghts the new president have to compromise with.